Development of a Novel Technique to Dissect the Mesentery That Preserves Mesenteric Continuity and Enables Characterization of the ex vivo Mesentery - Kumar, Ashutosh; Faiq, Muneeb A.; Krishna, Hare; Kishan, Vijay; Raj, Gladwin V.; Coffey, John Calvin; Jacob, Tony George (Frontiers in Surgery, 2020)
Introduction The conventional model of abdominal anatomy described multiple mesenteries. Dissection techniques were based on this. Recent studies demonstrate the mesentery is continuous from duodenojejunal flexure to anorectal level. Given this, it is important to update dissection techniques related to the mesentery in the cadaveric setting. Materials and Methods A technique of mesenteric dissection was developed and tested in a cohort of 20 adult human cadavers (12 male and 8 female). As the technique enabled excision of the mesentery as a single unit, it was possible to characterize the anatomy of the ex vivo mesentery. Results The technique developed enabled dissection of an intact and continuous mesentery in all cadavers examined. Examination of the ex vivo mesentery demonstrated that a mesoduodenum was present in all cases. The mesentery was continuous from the mesoduodenum to the mesorectum and ended at the level of the anorectal junction. Conclusions A technique was developed that reproducibly enabled dissection of an intact and continuous mesentery from from the duodenum to the anorectal junction. A mesoduodenum was consistently observed and noted to be in continuity with the remainder of the mesentery.